Le risque politique - Habib-Deloncle, Louis (Assurances)

(untitled) (HEC Montréal, 1991)
This article describes the complex nature of political risk in the present fast-changing international political and economic environment. Political risk insurance is available from two sources: government agencies and the private insurance market. The author examines the latter by reference to the nature of coverages, restrictions and conditions and analyses the most important roles of the insurer. Mr. Habib-Deloncle concludes that this era of liberalization in matters of international trade will provide new challenges for the insurance industry and that there are tremendous opportunities to meet the reinsurance needs of businesses as they grow and expand into new markets.